Efficacy and Safety of Stem Cell Transplantation in Rheumatoid Arthritis: ASystematic Review of Trials - Grady Krisandi (Indonesian Rheumatology Associantion, 2023)
Background: Rheumatoid arthritis (RA) is an autoimmune disorder thatdeteriorates the quality and function of the synovium membrane, resultingin chronic inflammation, pain, and progressive joint destruction. Based onprevious clinical research, stem cell transplantation has shown a promisingtherapeutic effect for RA based on its anti-inflammatory, immunomodulatory, and regenerative properties. This systematic reviewaims to evaluate the efficacy and safety of stem cell transplantation forrheumatoid arthritis therapy. Methods: A literature search was performedvia PubMed, ProQuest, EBSCOHost, EMBASE, SCOPUS, Cochrane, DOAJ,and clinicaltrial.gov databases, selecting studies that evaluated the effect ofstem cells on rheumatoid arthritis from inception to April 7, 2023. TheCochrane Risk of Bias was used to assess randomized controlled trials andROBINS-I was used to assess clinical trials. Results: 7 randomizedcontrolled trials (RCTs) and 12 non-randomized studies involving 682subjects were included in this review. Stem cell transplantation was relatedwith better outcomes based on significant improvement of the DAS28 score, HAQ score, ACR score, and laboratory parameters. There were no significant changes in safety parameters compared to the baseline value and control group. Fever, flu-like symptoms, nausea, and vomiting were the most frequently reported adverse effects. Nevertheless, this review revealed a moderate risk of bias and high heterogeneity of the efficacy outcomes of RCTs. Conclusion: Stem cell-based therapies provide clinical benefits for rheumatoid arthritis patients with satisfactory safety measures.